2012
DOI: 10.1111/bjh.12018
|View full text |Cite
|
Sign up to set email alerts
|

The multi‐kinase inhibitor TG02 overcomes signalling activation by survival factors to deplete MCL1 and XIAP and induce cell death in primary acute myeloid leukaemia cells

Abstract: SummmaryThe novel multi-kinase inhibitor TG02 has selectivity against cell cycle and transcriptional cyclin dependent kinases (CDKs) as well as fms-like tyrosine kinase receptor-3 (FLT3). Inhibition of transcriptional CDKs preferentially depletes short-lived proteins such as MCL1. We evaluated the in vitro toxicity of TG02 to primary acute myeloid leukaemia (AML) cells in the presence of survival signalling pathway activation by cytokines and fibronectin. One hundred nanomolar TG02 induced a median decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…We showed that using either agent at 100 nM was overall less effective than the combination of 50 nM of each drug (Figure 5C). Another point of note is that whereas the toxicity of ABT-199 reaches a plateau at around 25 nM, the toxicity of TG02 continues to increase, and the majority of cells are eradicated at 100 nM, as previously reported [17]. …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…We showed that using either agent at 100 nM was overall less effective than the combination of 50 nM of each drug (Figure 5C). Another point of note is that whereas the toxicity of ABT-199 reaches a plateau at around 25 nM, the toxicity of TG02 continues to increase, and the majority of cells are eradicated at 100 nM, as previously reported [17]. …”
Section: Resultssupporting
confidence: 69%
“…In this simplified scenario, TG02 as well as endogenous NOXA suppress the pro-survival function of MCL-1 and maybe of additional labile BCL-2 family pro-survival proteins (LBPP) [17, 20, 40]. ABT-199 and endogenous BAD suppress the pro-survival function of BCL-2 [14, 20, 40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG02 is a pyrimidine-based multi-kinase inhibitor that has been shown to target CDKs, JAK2 and FLT3. [31][32][33] More interestingly, TG02 has been shown to increase Bax activation and decrease expression levels of anti-apoptotic protein Mcl-1. 33 Therefore, the combination of carfilzomib and TG02 would allow us to target Mcl-1 via 2 different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Cell Signaling State Characterization. Antigen-or cytokineinduced phospho-signaling pathways (Hale and Nolan, 2006;Perez and Nolan, 2006) have been used as sensitive and early markers of cell activation in clinical studies to characterize cancers (Lim et al, 2012), measure intended targets (Strumberg et al, 2005;Crump et al, 2010;Brandwein et al, 2011;Pallis et al, 2012), and assess the off-target effects of drugs (Powers et al, 2011). However, it is increasingly recognized that a full appreciation of the nature and extent of cellular activation can be best assessed by simultaneously mapping several intersecting signaling pathways in single cells (Bonilla et al, 2008).…”
Section: Functional Assaysmentioning
confidence: 99%